The Effect of Coffee Consumption on Blood Pressure and Sleep Duration of Baristas in Majalengka - Hafidz Hilal Assegaf; Susianto Susianto; Mamlukah Mamlukah (Universitas Pendidikan Indonesia, 2021)
Drinking coffee is one of the most popular and loved by the community. The practice of drinking coffee has been associated with many health issues, both positive and negative. In association with their profession, baristas could consume more coffee, which is believed to affect their health. The objective of this study was to study the correlation between coffee consumption and baristas' blood pressure and sleep duration in Majalengka Regency. A cross-sectional design was used in this research. There were 40 baristas' in Majalengka involved in this experiment. A questionnaire and a sphygmomanometer were employed as instruments, and Spearman's instrument was used to examine the data. Respondents drank an average of 4 cups of coffee per day, had a systolic blood pressure of 117 mmHg, a diastolic of 77.75 mmHg. Sleep duration was negatively correlated with coffee consumption (p=0.012; c=-0.395). This study revealed that coffee consumption was not correlated with blood pressure (p=0.168). Coffee consumption has a negative relationship with sleep duration, which is controlled by the blood pressure variable, and it also does not influence blood pressure. In this study, we found the necessity of promoting healthy eating habits for baristas and cafe owners in the Majalengka Regency.